ANALYSIS OF STOCK MARKET REACTION DURING COVID-19 PANDEMIC IN INDONESIA IN 2021 (STUDY OF FINANCIAL SECTOR INDEX COMPANIES OF INDONESIA STOCK EXCHANGE) - Inayatul Muthmaninnah; Muhamamad Ramadhan (Jurnal Ekonomi, 2021)
Throughout 2021, the Indonesian stock market went through various dynamics due to Covid-19. This study aims to determine the stock market reaction to financial sector index companies using the variables Abnormal Return (AR), Security Return Variability (SRV), and Trade Volume Activity (TVA). The research time was conducted before and after the second spike in Covid on July 15, 2021, starting from the launch of IDX-IC on January 25, 2021 to July 15, 2021, and after the peak on July 15, 2021 to December 31, 2021. The type of research used is quantitative with secondary data sources. The number of samples was 51 banking sub-sector companies from 104 financial sector index companies. Data analysis was carried out using descriptive tests, normality tests, paired sample t-tests if the data was normally distributed and Wilcoxon signed rank tests if the data was not normally distributed. The results obtained were that there was no significant difference in AR, SRV, and TVA in the period before and after the second peak of Covid-19.